2023
DOI: 10.1021/acssuschemeng.2c07590
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen Bonds on CO2 Capture by Functionalized Deep Eutectic Solvents Derived from 4-Fluorophenol

Abstract: Deep eutectic solvents (DESs) have received a great amount of attention for CO 2 uptake due to their unique properties. Here, deep eutectic solvents (DESs) based on 4-fluorophenol-derived superbase ionic liquid are studied for CO 2 capture. The ionic liquid used is [DBUH][4-F-PhO], formed by 1,8-diazabicyclo[5.4.0]undecane-7-ene (DBU) and 4-fluorophenol (4-F-PhOH). The DESs are obtained by mixing [DBUH][4-F-PhO] with ethylene glycol (EG) or 4-F-PhOH. Surprisingly, [DBUH][4-F-PhO]-EG DESs present a much higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The presence of versatile interactions in DESs significantly increases the solubility for small molecules, which is favorable for the adsorption and conversion of small molecules in electrocatalytic reactions. 62–65 Besides, interactions in DESs could construct supramolecular networks to control the growth direction of materials and could also play significant roles in activating reactants and stabilizing intermediates, 30,40,66–68 making DESs promising candidates as electrolytes for electrocatalysis.…”
Section: Features Of Dess Applicable To Electrocatalysismentioning
confidence: 99%
“…The presence of versatile interactions in DESs significantly increases the solubility for small molecules, which is favorable for the adsorption and conversion of small molecules in electrocatalytic reactions. 62–65 Besides, interactions in DESs could construct supramolecular networks to control the growth direction of materials and could also play significant roles in activating reactants and stabilizing intermediates, 30,40,66–68 making DESs promising candidates as electrolytes for electrocatalysis.…”
Section: Features Of Dess Applicable To Electrocatalysismentioning
confidence: 99%
“…In general, DESs are prepared by simply mixing of two or more components, including both hydrogen bond acceptors (HBAs) and hydrogen bond donors (HBDs), to form a solution with a melting point lower than that of any of its components by means of hydrogen bonding interactions. Organic amines and azoles are widely used to synthesize ILs to capture CO 2 , which can also be used as HBDs and HBAs. Three types of the most studied DESs for CO 2 capture are as follows: amino-based functionalized DESs, azole-based functionalized DESs, and super base functionalized DESs. Due to the low cost and highly efficient capture of CO 2 by amines, amino-based functionalized DESs have been widely investigated. Zhang et al selected monoethanolamine (MEA) as a HBD and synthesized several 1-butyl-3-methylimidazolium chloride (BmimCl):MEA DESs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the mole absorption capacity of [TETA]­Cl/EG DES increased from 0.75 mol CO 2 /mol [TETA]Cl to 1.456 mol CO 2 /mol [TETA]Cl as the molar ratio of EG to [TETA]Cl increased from 1:1 to 3:1. Additionally, EG has also been reported to be involved in the chemical capture of CO 2 in super base functionalized DESs, in which EG acted as a chemical interaction site and formed carbonate with CO 2 after being deprotonated by the super base. , So, in this work, EG was selected as the HBD to form DES with aromatic amines.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, for the [Et 4 N][Car]-4CH 3 -Im (4CH 3 -Im: 4-methylimidazole) system, CO 2 reacted with the anion [Car] − , but did not react with 4CH 3 -Im. In addition, superbase-derived anion-functionalized DESs were also explored for CO 2 capture, such as [DBUH][Im]-EG (DBU: 1,8-diazabicyclo-[5,4,0]undec-7-ene) [ 42 ], [DBUH][MLU]-EG (MLU: methyl urea) [ 43 ], [DBNH][Triz]-EG (DBN: 1,5-Diazabicyclo[4.3.0]non-5-ene) [ 44 ], [DBUH][Car]-EG [ 45 ], DBN-EU (EU: 2-imidazolidone) [ 46 ], [DBUH][4-F-PhO]-EG(4-F-PhO:4-Fluorophenolate) [ 47 ], ternary DESs [DBUH][4-F-PhO]-4-F-PhOH-EG [ 47 ], and DBN-BmimCl-Im [ 48 ]. According to the results reported in the literature, it can be found that the components of DESs greatly affect the CO 2 absorption behaviors of functionalized DESs.…”
Section: Introductionmentioning
confidence: 99%